Evaluation of quality of life after paediatric cochlear implantation - Byčkova, Jekaterina; Simonavičienė, Justė; Mickevičienė, Vaiva; Lesinskas, Eugenijus (Acta medica Lituanica, 2019)
Background. Cochlear implantation (CI) is the main treatment method for deaf children. CI influences not only communication, but also psychosocial outcomes in children with severe to profound hearing loss. Focusing on issues specific to CI (e.g., self-reliance, social relations, education) may provide a more accurate and relative view of functional status of paediatric cochlear implant users. The objectives of this study were to translate into Lithuanian and adapt an international questionnaire of the quality of life after cochlear implantation and to evaluate parental perspectives regarding CI and the child’s progress after a minimum of two years after surgery. Materials and methods. The parental questionnaire The Children with Cochlear Implants: Parental Perspectives CCIPP was used to evaluate the quality of life following cochlear implantation. The questionnaire includes 74 items covering two main domains: decision-making (26 items) and the outcomes of implantation (48 items). Quality of life is estimated according to the scores of eight sub-domains: communication, general functioning, well-being, self-reliance, social relations, education, effects of implantation, and supporting the child. Results. The paediatric sample consisted of 11 (39%) girls and 17 (61%) boys, whose mean age at the time of cochlear implantation was 2.41 ± 2.25 years, mean duration of the implant use 3.7 ± 1.3 years. All the grand means in the outcomes of implantation domain exceeded 3 on the 5-point scale, meaning that parents viewed the quality of life of their children as either average or better. Parents rated the sub-domains of communication (3.90 ± 0.77 points), social relations (4.05 ± 0.41), and supporting the child (3.89 ± 0.49) most positively. Conclusions. According to parents, the quality of life improves after the cochlear implantation, especially in the fields of communication, social relations and supporting the child.